ANALISIS REALITA DAN PERBANDINGAN REGULASI NEGARA DENGAN HUKUM ISLAM TENTANG PERNIKAHAN BEDA AGAMA DI INDONESIA - Rana’a Ardjunika Adeyanti; Nabila Alisa’diyah; Melani Syukria Jamil (Journal Khafi : Journal Of Islamic Studies, 2025)
Interfaith marriage remains a debated issue in Indonesia due to differences between religious rules and state law. In Islam, marriage is considered an act of worship and must follow strict rules, including marrying within the same faith. According to Indonesia’s 1974 Marriage Law, a marriage is only valid if it follows the religious laws of both parties. However, interfaith marriages still occur and are increasing. This study explores university students’ views on this topic. Using a qualitative case study approach, 20 students from different backgrounds were surveyed. Results show that 65% believe interfaith marriages can be legally registered, and most have a tolerant attitude. This highlights a gap between the law and social reality. The study suggests the need for updated laws that balance respect for religious values and social diversity, and calls for open dialogue between the government, religious leaders, and society to create fairer and more inclusive regulations.